1999
DOI: 10.1016/s0022-5347(01)61738-5
|View full text |Cite
|
Sign up to set email alerts
|

The Globoseries Glycosphingolipid Sialosyl Galactosyl Globoside is Found in Urinary Tract Tissues and is a Preferred Binding Receptor In Vitro for Uropathogenic Escherichia Coli Expressing Pap-Encoded Adhesins

Abstract: Women with a history of recurrent Escherichia coli urinary tract infections (UTIs) are significantly more likely to be nonsecretors of blood group antigens than are women without such a history, and vaginal epithelial cells (VEC) from women who are nonsecretors show enhanced adherence of uropathogenic E. coli isolates compared with cells from secretors. We previously extracted glycosphingolipids (GSLs) from native VEC and determined that nonsecretors (but not secretors) selectively express two extended globose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0
4

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 44 publications
1
37
0
4
Order By: Relevance
“…It has been reported that canine ExPEC strains typically do not express P fimbriae and thus are fundamentally different from human ExPEC strains (74), that they express P fimbriae and hence are similar to human ExPEC strains (71), and that they express variant forms of P fimbriae that are dissimilar to the P fimbriae of most human ExPEC strains (5,7,36,37,41,56,57), but may be present in some human isolates (36,37,41,56,57). These investigations were done before assays for the three papG alleles were generally available (12,16), before the epidemiological association of papG allele III with human cystitis had been demonstrated (12,23,59), and before it was known that receptors for PapG variant III are not confined to nonhuman hosts (5,7,46,62,63) or to humans of the A blood phenotype (36,37,56) but are present generally in humans, including within the human urogenital tract (e.g., as sialosylgalactosyl-globoside) (31,32,60,64). These more recent developments, together with the results of the present study, clarify several points.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that canine ExPEC strains typically do not express P fimbriae and thus are fundamentally different from human ExPEC strains (74), that they express P fimbriae and hence are similar to human ExPEC strains (71), and that they express variant forms of P fimbriae that are dissimilar to the P fimbriae of most human ExPEC strains (5,7,36,37,41,56,57), but may be present in some human isolates (36,37,41,56,57). These investigations were done before assays for the three papG alleles were generally available (12,16), before the epidemiological association of papG allele III with human cystitis had been demonstrated (12,23,59), and before it was known that receptors for PapG variant III are not confined to nonhuman hosts (5,7,46,62,63) or to humans of the A blood phenotype (36,37,56) but are present generally in humans, including within the human urogenital tract (e.g., as sialosylgalactosyl-globoside) (31,32,60,64). These more recent developments, together with the results of the present study, clarify several points.…”
Section: Discussionmentioning
confidence: 99%
“…These more recent developments, together with the results of the present study, clarify several points. They provide an explanation for the characteristic NS phenotype of pap-positive canine ExPEC strains (41), which is probably due to desialation by neuraminidase of sialosyl-galactosyl-globoside, the major receptor on human erythrocytes for the variant III PapG adhesin (32,56,60,64). They account for the seemingly discrepant MRHA results reported for canine ExPEC strains by various investigators (5,7,56,57,62,71,74), since the observed phenotypic variability is consistent with conflicting published data regarding PapG variant III (15,28,32,36,62).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pap operon encodes pyelonephritis-associated (P) fimbriae that allow uropathogenic E. coli to bind Gal␣(1-4)Gal moieties present in glycolipids expressed by kidney epithelial cells (34,310,312,318,320,321). P fimbriae are composed of a rigid helical fimbrial shaft that ends in a flexible tip fibrillum (46, 185).…”
Section: The -Fimbriae: P-fimbria-like Operonsmentioning
confidence: 99%
“…Globo-series GSL are also important host factors in the pathophysiology of several infectious diseases (36). The colonization of epithelial cells by Streptococcus suis, Escherichia coli, and Pseudomonas aeruginosa is through the recognition of globo-series GSL (37)(38)(39). Gb4 serves as the receptor for parvovirus B19, and Gb3 is required for the CD4/CXCR4-dependent fusion of HIV (40,41).…”
Section: Discussionmentioning
confidence: 99%